Bringing justice to unacceptable health care services?: Street-level reflections from urban South Africa - Harris, Bronwyn (International journal of transitional justice, 2014)
Transforming repressive institutions into respected instruments of justice is necessary for the social reconstruction of fragile and postconflict states. Yet, little attention has been given to the role of health systems in facilitating such change. We situate South Africa’s right to access health care as part of a broader sociopolitical endeavour to ‘bring justice’ in the aftermath of apartheid and argue that street-level bureaucrats tasked with delivering health services are a gauge of both individual and institutional transformation. Using cases from two urban areas, we consider responses to inaccessible antiretroviral therapy, tuberculosis treatment and maternal deliveries and ask whether these ameliorate or compound access barriers. We also explore some conditions for bringing justice to street-level interactions. Our cases suggest that, if left unchallenged, negative street-level bureaucracy may compound inaccessible care for patients and perpetuate a wider culture of disempowerment, deprivation and poverty - ongoing structural violence - for citizens, while positive provider practices may be ameliorative. Strengthening street-level accountability and engendering respectful, empathetic provider practices is consequently vital to improving access to services and contributing more generally to the restoration of justice and health in society.